PENINGKATAN HASIL BELAJAR IPAS KOMPONEN BIOTIK DAN ABIOTIK MELALUI MODEL CTL BERBANTU CANVA - Fauzan, Mochamad Fadhillah Yusup; Kamila, Shafa Tasya; Sanjaya, Siti Novelinda; Sudrajat, Dina Marlina; Santoso, Aam Amalia; Nugraha, Rana Gustian (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
ABSTRACT This study was conducted to improve students’ learning outcomes on the topic of biotic and abiotic components in IPAS (Integrated Science and Social Studies) learning by integrating the Contextual Teaching and Learning (CTL) model with Canva media. The research employed Classroom Action Research (CAR), which was implemented in two learning cycles involving third-grade students at SDN Sindangpalay. Data collection techniques included learning outcome tests, observations of learning activities, and documentation. The implementation of the CTL model focused on integrating learning concepts with students’ real-life experiences through discussion, exploration, and problem-solving activities, strengthened by the use of Canva as a visual medium for presenting learning materials. The results showed that the application of the CTL model supported by Canva media significantly improved students’ learning outcomes and increased active student engagement during the learning process. Students demonstrated better conceptual understanding and higher levels of participation in learning activities presented in a contextual and visual manner. Canva media helped teachers deliver learning materials more clearly and attractively and played an important role in visualizing abstract concepts to make them easier to understand. Based on these findings, it can be concluded that the application of the CTL model assisted by Canva media is effective in improving the quality of meaningful IPAS learning and has a positive impact on enhancing elementary school students’ learning outcomes on the topic of biotic and abiotic components. ABSTRAK Penelitian ini dilakukan untuk meningkatkan capaian hasil belajar peserta didik pada materi komponen biotik dan abiotik dalam pembelajaran IPAS dengan mengintegrasikan model Contextual Teaching and Learning (CTL) dan media Canva dalam pembelajaran. Metode yang digunakan dalam penelitian ini adalah Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus pembelajaran pada siswa kelas III SDN Sindangpalay. Teknik pengumpulan data dalam penelitian ini meliputi tes hasil belajar, observasi aktivitas pembelajaran, dan dokumentasi. Penerapan model CTL difokuskan pada pengintegrasian konsep pembelajaran dengan pengalaman kehidupan sehari-hari siswa melalui kegiatan diskusi, eksplorasi, dan pemecahan masalah yang diperkuat dengan penggunaan media Canva sebagai sarana visualisasi materi pembelajaran. Berdasarkan hasil penelitian, penerapan model CTL yang didukung oleh media Canva terbukti mampu meningkatkan hasil belajar siswa secara signifikan serta meningkatkan keterlibatan aktif peserta didik selama proses pembelajaran berlangsung. Siswa memperlihatkan pemahaman konsep yang lebih baik serta keterlibatan yang lebih tinggi dalam pembelajaran yang disajikan secara kontekstual dan visual. Media Canva membantu guru dalam menyajikan materi pembelajaran secara lebih jelas dan menarik dan berperan dalam memvisualisasikan konsep-konsep abstrak agar lebih mudah dipahami. Berdasarkan hasil penelitian, dapat disimpulkan bahwa penerapan model CTL berbantu media Canva efektif dalam meningkatkan kualitas pembelajaran IPAS yang bermakna dan berdampak positif terhadap peningkatan hasil belajar peserta didik sekolah dasar pada materi komponen biotik dan abiotik.